Drawing method with crayons as a medium of expression and imagination for children - Ariani, Ariani; Werdina, Woro Asty; Nugrahadi, Gihon; Soeriaatmadja, Rully (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2020)
Drawing is a medium of expression and a part of children’s creative and imaginative process. Children can create, share ideas, visualize and realize their imagination through drawing. Drawing with crayons is familiar to children but this does not apply to the children of age between 5 – 12 years old who live in Karawaci district, Indonesia. These children did not have the opportunity to learn additional skills through informal education due to their families’ financial constraint. The purpose of this activity is to provide training in the right drawing methods and to train children to be creative in dealing with the limitations of the financial conditions. A qualitative method with a case study approach is used to achieve the objectives and determine the answers to the problems encountered in this research. Out of the five methods introduced, the blocking and mixing methods were the most preferred techniques by the children because it was easy to use and produced drawing with bright colours which represent their expression and imagination.